Lightweight MgB2 superconducting 10 MW wind generator. (21st December 2015) - Marino, I; Pujana, A; Sarmiento, G; Sanz, S; Merino, J M; Tropeano, M; Sun, J; Canosa, T
Abstract: The offshore wind market demands a higher power rate and more reliable turbines in order to optimize capital and operational costs. The state-of-the-art shows that both geared and direct-drive conventional generators are difficult to scale up to 10 MW and beyond due to their huge size and weight. Superconducting direct-drive wind generators are considered a promising solution to achieve lighter weight machines. This work presents an innovative 10 MW 8.1 rpm direct-drive partial superconducting generator using MgB2 wire for the field coils. It has a warm iron rotor configuration with the superconducting coils working at 20 K while the rotor core and the armature are at ambient temperature. A cooling system based on cryocoolers installed in the rotor extracts the heat from the superconducting coils by conduction. The generator's main parameters are compared against a permanent magnet reference machine, showing a significant weight and size reduction. The 10 MW superconducting generator concept will be experimentally validated with a small-scale magnetic machine, which has innovative components such as superconducting coils, modular cryostats and cooling systems, and will have similar size and characteristics as the 10 MW generator.